Golden Holocaust : Origins of the Cigarette Catastrophe and the Case for Abolition. - Proctor, Robert, 1954- (University of California Press, 2012)
The cigarette is the deadliest artifact in the history of human civilization. It is also one of the most beguiling, thanks to more than a century of manipulation at the hands of tobacco industry chemists. In Golden Holocaust, Robert N. Proctor draws on reams of formerly-secret industry documents to explore how the cigarette came to be the most widely-used drug on the planet, with six trillion sticks sold per year. He paints a harrowing picture of tobacco manufacturers conspiring to block the recognition of tobacco-cancer hazards, even as they ensnare legions of scientists and politicians in a.
Keywords: Tobacco industry -- United States -- History.; Tobacco use -- Health aspects.; Smoking -- Psychological aspects.; Persuasion (Psychology); Government Regulation -- United States -- History.; Tobacco Industry -- United States -- History.; History, 20th Century -- United States.; Persuasive Communication -- United States.; Smoking -- adverse effects -- United States.; Smoking -- psychology -- United States.; Tobacco Industry -- economics -- United States.; Tobacco Industry -- economics; History, 20th Century; Persuasive Communication; Smoking -- adverse effects; Smoking -- psychology; Tobacco Industry -- history; Government Regulation -- history; United States; Tabac -- Industrie -- États-Unis -- Histoire.; Tabagisme -- Aspect psychologique.; Médecine -- Histoire -- 20e siècle.; Communication persuasive.; PSYCHOLOGY -- Psychopathology -- Addiction.; SELF-HELP -- Substance Abuse & Addictions -- General.; MEDICAL -- History.; Smoking -- Psychological aspects; Tobacco industry; Tobacco use -- Health aspects; History